Kampung Sungai to Kerala: A deadly zoonotic trail encroaching diverse geography (Anwer Khan Modern Medical College Journal, 2023)
Background: Nipah virus is an emerging zoonotic virus which causes fatal encephalitis in South-East Asia region since 1999. Thereafter, it is prevalent almost every year in the different parts of Bangladesh and India. The aims of this analysis to describe the epidemiological patterns of the Nipah infection and also to highlight the factors for the recurrent outbreak in this region.Materials & methods: Intensive web searching was done for documents and journals on Nipah Virus infection and Nipah outbreak from 1999 to 2018. A total of 279 research documents were found and about 40 papers, especially the PubMed indexed sources and newsletters distributed by different public health agencies were selected for the meta-analysis. Information gathered from the selected journals and documents were described in text and figures.Results: The analysis revealed that fruit bats of the Pteropus genus are the natural hosts of the virus. After documentation of only outbreak in Malaysia in 1999, Nipah virus struck in Meherpur in 2001 for the first time and thereby, creating a public health issue every year. Very recently, this deadly zoonotic virus caused fatality in Kerala, India which is far away from its usual prevalent region. It starts with the ingestion of Nipah infected raw date palm sap and direct contact with the infected person. Early diagnosis and strict isolation is the mainstay to prevent an outbreak. Strong public health measures can able to reduce both the frequency and mortality of the disease.Conclusions: Nipah virus infection is now one of the ten priority diseases listed by the World Health Organization considering its high fatality rate. However, effective health education and infection control practice is still considered as the mainstay of prevention of future Nipah outbreak.AKMMC J 2021; 12(1) : 52-57